The Importance of Assesment in Online Learning Education - Muhammad Taufik Ihsan; Widya Nur Afiati; Sefrizel Rahayu; Yeni Elma Fitri (English Instruction, 2020)
The aims of this study to identify the importance of assessment in online learning. This article is motivated by several problems that occur in online learning, one of the problems that occurs is the difficulty in managing time between teachers and students. This research used literature study. This online learning assessment identified of understanding and sharing information. The results of the study found that students need online learning which helps them more effective and effecient, so that online learning becomes of high quality and provides opportunities that provide benefits to students. In addition, online learning has an effect on learning achievement, because online learning is less effective because there are not many students who understand the material presented online. Because of this , online learning must be able to manage time, and each student must focus when the lecturer explains the learning material.